Peace-Building and Stability after Civil Wars: The Cases of Angola and the Democratic Republic of the Congo - Elsharkawy, Ali (AUC Knowledge Fountain, 2024)
Why do some rebel groups successfully establish stable and sustainable states after civil wars, while others fail? Angola and the Democratic Republic of the Congo are two African countries that experienced long and bloody civil wars. Despite the commonalities, the two cases strongly diverged in the political outcomes after civil war. Angola successfully made the transition to stability and prosperity, while the DRC slipped back into violence. This thesis compares and contrasts between the two peace- building processes in both countries. The results illustrate that two main variables made the difference between the two cases, the geography of the capital city and the strength of state institutions. The two variables allowed the regime in Angola to defeat the opposition and establish control over the whole territory, thereby independently implemented locally crafted peace building-process. On the other side, external intervention in the peace-building process undermined stabilization efforts.